ANTI-Lentivirus, Brucella abortus AND B. ovis ANTIBODIES IN SMALL RUMINANTS RAISED IN PERNAMBUCO AND BAHIA - RODOLFO DE MORAES PEIXOTO; GRACE BARBOSA DOS SANTOS; EVANDRO SANTOS AMANSO; MARIA DA CONCEIÇÃO AQUINO DE SÁ; RENATA DE MORAES PEIXOTO ARAÚJO; MATEUS MATIUZZI DA COSTA (Revista Caatinga, 2016)
Goat and sheep production in the semi-arid northeast of Brazil has shown great economic potential. However, health problems can compromise the productivity of these animals. Given the scarcity of studies about the occurrence of these diseases, the aim of the present study was to analyze the serological diagnosis of anti-Brucella and anti-lentivirus antibodies among small ruminants in municipalities located in the Brazilian states of Bahia and Pernambuco. The samples were collected from local slaughterhouses and dairy farms. In total, 997 serum samples from animals in slaughterhouses and dairy herds were collected. In order to diagnose the caprine arthritis encephalitis virus (CAEV), the samples underwent agarose gel immunodiffusion (AGID) testing. The buffered acidified antigen test (goats) and agarose gel immunodiffusion test (sheep) were used to detect anti-Brucella abortus and B. ovis antibodies following the methodology recommended by the Institute of Technology of Paraná (TECPAR). With anti-CAEV antibodies, seropositivity rates of 4.1% and 2.2% were recorded for animals from the slaughterhouses and dairy farms, respectively. None of the animals (goats or sheep) were positive for anti-B. abortus antibodies. With B. ovis, a seropositivity rate of 6.5% (n = 13) was recorded among the 199 sheep serum samples. Results of the present study confirmed the presence of the CAE virus in the meat and dairy herds studied, although the prevalence was low. Natural infection by B. abortus did not occur in the goat and sheep herds assessed. Seropositivity for B. ovis was confirmed, although prevalence was low. Direct tests are required to diagnose ovine brucellosis.